The Dangerous Level of Landslide at the Hill Area of Maninjau Lake at Tanjung Raya District of Agam Regency. Skripsi. Study Program of Geography STKIP PGRI West Sumatera, Padang. - Sari, Yanti Puspita; Juita, Erna; Keslan, Widya Prari (STKIP PGRI Sumbar, 2013)
In the utilization of area by the human should pay attention the limited area exploitation due to the larger exploitation will affect to the area. For example the landslide, is a frequently natural phenomenon occurred. This research aim to know the slope, length of slope, texture, structure, permeability, rock decay, rainfall rate, area usage and the potency of landslide around the vicinity of Manainjau Lake to each existing area at the at Tanjung Raya District of Agam Regency. For each existing area in the research area consisted of six unit area and sample was taken by purposive sampling through related consideration where the sample was taken have already represented each various area unit that has already established. The data analysis used descriptive analysis that is an analysis in the form of comparative table between the slope, length, texture, structure, permeability, rock decayed, rainfall, the area usage and landslide potency in the vicinity of Maninjau lake. The result of research showed that: 1) the slope in the research area have variation, those are started from 2 fold level with the slope about (16%), 3 fold level with the slope about (35%), 4 fold level with the slope about (42%). 2) the length of slope was started from the criteria of length (140 m) up to the longest due to trigger the landslide. 3) the physical character of soil to the research area was generally sensitive to have landslide because its texture of muddy and sandy and structure granular and permeability started from the lowest, speed, rather speed, the decay level was strong decay, rainfall at the station of Manggopoh was the highest with amount about 158,72 mm/years, 4) the area usage have variation was started from the bush to the forest, agriculture area and farming area. 5) By having risky level of landslide danger which consisted of 1. Middle level to the area unit 1 (V1 Qamj.IISbl.Dyst, to the sample 2 (V1.Qamj.II.Ht.Hap) sample 3 (VI.Qamj.II.Kc.Ter) and sample 4 (VI.Qamj. IV.Ht.Hap) sample 5 (V3 Qamj.IV.Ht.Dyst) and sample 6 (V3.Qamj.IV.Sw.ter)Key words: Danger, Landslide, Slope, Maninjau Lake.